Language teachers as leaders: A case study of teacher leaders in the Arabian Gulf - Sayyed Rashid Ali Shah (Cogent Education, 2020)
This study introduces the construct of teacher leadership in the Saudi EFL higher education context. The key aims of this study are to understand the notion of teacher leadership from the EFL teachers’ perspective, to identify various leadership roles EFL teachers undertake in this context, and to explore challenges associated with teacher leadership practices in the hierarchical leadership structures of Saudi Arabian universities. The participants of the study were 12 EFL teachers who shared their perceptions of teacher leadership practices in the Saudi EFL context. Two data collection tools were used to gather qualitative data; semi-structured interviews and open-ended questionnaires. The data were thematically analysed using NVivo10 that led to four major categories and one key theme. The findings suggest that teacher leadership is a novel concept in the Saudi EFL context and teacher leaders operate in hierarchical leadership structures. Interestingly, their wide range of instructional and operational leadership roles are similar to the three historical waves of teacher leadership in the US school context. The impact of hierarchical structures on teacher leadership practices is evidently found as EFL teacher leaders encounter several challenges, such as heavy administrative workload and lack of autonomy. Nevertheless, their intragroup shared leadership practices help them overcome these challenges and contribute to organizational effectiveness.